The Pains of Imprisonment and Contemporary Prisoner Culture in Canada - McKendy, Laura (The prison journal, 2021)
Drawing on interviews conducted with former federal and provincial prisoners in Ontario, Canada, we consider how the unique social conditions in these two institutional contexts shape interpersonal dynamics and the prisoner experience. Despite notable differences in federal versus provincial prisoner culture, we suggest that prisoners in both contexts lived in environments marked by uncertainties and risk; in response, they tended to adapt to a highly individualistic orientation toward doing time. Based on our analysis, we complicate the conceptualization of prisoner culture as primarily serving an adaptive function, suggesting the prison social climate may actually drive the most salient pains of imprisonment.